Prospects of Torsen Differential in Four Wheel Drive Automobile Transmission System. (2018) - Suhane, Amit; Rana, R.S.; Purohit, Rajesh
Abstract: Four wheel drives possess an added advantage of maneuvering the driven vehicle at ease in adverse situations like slippery road, terrain, off road conditions. In present scenario of automobile transmission systems, automatic and manual changing of two wheel drive (2WD) to four wheel drive (4WD) is used. In manual operation the driver changes the lever as 2WD-4WD or as low-high gearing and the automated operation is executed by the sensors sensing the road conditions. Extensive researches on automobiles have shown that transmission and drive losses accounts for the significant proportions. Manufacturers are constantly developing methods and techniques to improve handling and performance of modern four wheel drives. The present research work evaluates the importance of torsion differential amongst the available compatible differentials in drive shifts owing to its dominant characteristics like it being a self-locked type, purely mechanical, requiring lesser maintenance, 'no time delay' before coming into action etc. But switching or changing from manual to automatic mode; the drive mechanism becomes complicated and costly due to large components. Therefore, need of hour is to select that drive and mechanism which suits the requirements and corresponding applications at reduced costs and components. This research signifies better prospects in terms of automatic switching of drive, reduced driver fatigue, enhanced battery life, reduced accidents etc. which is always appreciable.